Relationship banking within the Irish SME sector and its implication - Aoife Hanley; Sheila O'Donohoe (Kiel Institute for the World Economy (IfW), 2009)
Relationship banking involves the provision of financial services by an intermediary that a) invests in obtaining customer-specific information, often proprietary in nature; and b) evaluates the profitability of these investments through multiple interactions with the same customer over time and/or across products (Boot, 2000). We assess the presence and impact of relationship banking from an Irish SME perspective.We trace how significant patterns can be seen across several dimensions of the lender/business relationship using data for the year 2005. These dimensions include the duration of lender/business relationships and the cost of finance.
Keywords: G21; L26; 330; Relationship lending; Hausbank; Kredit; Bank; Klein- und Mittelunternehmen; Lieferanten-Kunden-Beziehung; Kapitalkosten; Irland